Exploring Echinococcus Infection in the Spinal Cord: Clinical Manifestations and Management Insight - Erald Giovanny Hasiholan Simatupang; Dhea Ivanka (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Echinococcus infection in the spinal cord can lead to various complications, including compression of the spinal cord. In some cases, Echinococcus infection can result in the formation of dumbbell structures within the spinal cord, extending into the paravertebral region. This type of infection is characterized by a high recurrence rate, ranging from 50% to 100%. This study used reliable and important scientific databases like PubMed, ScienceDirect, Google Scholar, as well as official databases from health organizations. Furthermore, studies have shown that individuals with preexisting conditions like pressure ulcers are at an elevated risk of postoperative infections following spinal cord surgery. Echinococcus infection in the spinal cord can have serious consequences such as compression and the formation of complex structures. Understanding the risk factors associated with postoperative infections and the persistence of viral infections in the spinal cord is crucial for effective management and treatment strategies in affected individuals.